Effect of integrated potassium nutrition on Fusarium wilt tolerance in apple bananas - Nowembabazi, Anna; Taulya, Godfrey; Tinzaara, William; Karamura, Eldad (Academic Journals, 2021)
This study describes the effects of potassium on tolerance to Fusarium wilt in apple bananas using chlorophyll content, stomatal conductance and severity of Fusarium wilt symptoms as indicators.